EQUALITY REVOLUTION: FEMINIST THEORY AND SOCIAL TRANSFORMATIONS - Latova, Maria; Baklanova, Nataliia (SWorld-Ger Conference proceedings, 2023)
The role of women in society has always been the subject of much debate, both from the feminist movement and from opposing sides. However, we see great results that women have achieved through the acquisition of broad rights. Feminist theory still remains